The Influences of Organizational Unlearning and Business Model on Performance: fsQCA Approach - Andrey Andoko (Goodwood Publishing, 2026)
Purpose: This study aims to identify the configurational factors of organizational unlearning and business model innovation as the core factors that influence firm performance with an innovativeness orientation. Research Methodology: This study applies Fuzzy-set Qualitative Comparative Analysis (fsQCA) with 162 respondents at the firm level, collected from the top management of the traditional media industry. Results: No single factor contributes independently as a sufficient predictor of high firm performance in old and digital businesses. The joint presence of changing routines, innovating revenue models, and adapting cost structures is the most influential factor in achieving high firm performance in old and digital businesses. Conclusions: No single factor influences firm performance, indicating the existence of equifinality. The joint configuration of innovation, discarding old mind-sets, changing routines, adapting cost structures, and innovating revenue models will drive firm performance and ensure business sustainability. Limitations: Reliance on questionnaire data may cause bias, and the number of samples is limited because the study collected data at the firm level. Contributions: This study enriches the extant fsQCA method in organizational and entrepreneurship research.